2000
DOI: 10.1177/107110070002101105
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice Patterns in the Treatment of Charcot Foot

Abstract: Treatment of Charcot foot osteoarthropathy has emerged as a major component of the American Orthopaedic Foot and Ankle Society (AOFAS) Diabetes 2000 Initiative. A two-part survey described treatment patterns and current footwear use of patients with Charcot osteoarthropathy of the foot and ankle. In the first part, 94 consecutive patients with a history of Charcot foot and ankle presenting for care were questioned on their foot-specific treatment and current footwear use. A history of diabetic foot ulcer was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 4 publications
1
36
0
2
Order By: Relevance
“…Frykberg et al recommended a non-weightbearing period of 8–12 weeks to avoid trauma to the affected foot [34]. Other investigators allowed weightbearing when the foot was placed in a cushioned device [10, 36–38]. De Souza et al showed that protected weightbearing in a TCC does not initiate new foot ulcers in the treatment of a Charcot foot [10].…”
Section: Discussionmentioning
confidence: 99%
“…Frykberg et al recommended a non-weightbearing period of 8–12 weeks to avoid trauma to the affected foot [34]. Other investigators allowed weightbearing when the foot was placed in a cushioned device [10, 36–38]. De Souza et al showed that protected weightbearing in a TCC does not initiate new foot ulcers in the treatment of a Charcot foot [10].…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Autonomic neuropathy is well known to alter vasoregulation, leading to increased bone reabsorption and osteopenia, allowing minor trauma to cause fractures, dislocation, and joint collapse. 2,8 One study of 261 patients with diabetes found abnormalities on cardiovascular autonomic testing in 6% to 31% of those without neuropathy, 16% to 45% with subclinical neuropathy, 22% to 59% with symptomatic neuropathy, and 67% to 100% with peripheral neuropathy and autonomic symptoms. 9 Support for this theory includes studies on peripheral circulation in patients with small fiber autonomic neuropathy, which showed increased blood flow in diabetics versus nondiabetics.…”
Section: Pathogenesis the Neurovascular Theorymentioning
confidence: 98%
“…There have been various treatment regimens advocated by several authorities [89,90] with no single regimen emerging as the most effective. This is largely due to the paucity of randomised, double-blind, controlled trials looking into the most efficacious way of treating CN.…”
Section: Managementmentioning
confidence: 99%